Behavioral Drivers of Gold Investment Intentions: The Role of Income, Gold Prices, and Islamic Financial Behavior - Adetia Dara Ayu; Marliyah; Imsar (FEBI IAIN Langsa, 2026)
This study aims to examine the effect of gold prices, income, and Islamic financial behavior on public interest in investing in gold jewelry in Ujung Negeri Hulu Village, Bintang Bayu District, Serdang Bedagai Regency. This research uses a quantitative approach with a population of 485 people and a sample of 83 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that partially, gold prices, income, and Islamic financial behavior have a positive and significant effect on investment interest. Simultaneously, these variables also have a significant effect on investment interest. The coefficient of determination (R²) is 0.589, indicating that 58.9% of the variation in investment interest can be explained by the independent variables, while 41.1% is influenced by other factors outside the model. This study contributes to the literature by integrating economic and Islamic behavioral factors in explaining investment interest in rural communities.